SYSTEMIC AND LOCAL METABOLIC CHANGES IN INTERSTITIAL LUNG INJURY - Tursunov, D.Kh.; Sabirova, R.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2026)
Background: Interstitial lung injury is accompanied by significant metabolic disturbances affecting both local pulmonary structures and systemic homeostasis. However, the relationship between these changes remains insufficiently studied. Material and methods: The study was performed on 64 rats with experimentally induced interstitial lung injury via chronic tobacco smoke exposure. Metabolic parameters were assessed in serum and bronchoalveolar fluid, including phospholipid fractions and lipid metabolism indices. Lipids were extracted by the Folch method and analyzed using thin-layer chromatography. All procedures complied with international ethical standards. Results: Experimental interstitial lung injury was associated with significant metabolic disturbances at both local and systemic levels. In bronchoalveolar fluid and blood, a decrease in structural membrane components and an increase in membrane degradation products were observed, indicating destabilization of cellular membranes. In addition, pronounced alterations in lipid metabolism were detected, including elevated levels of total cholesterol, triglycerides, and low-density lipoproteins, along with a decrease in high-density lipoproteins. Pharmacological correction contributed to partial normalization of the studied parameters, with the most significant effect observed in combined therapy, where values approached those of intact animals. Pharmacological correction partially restored metabolic balance, with the most pronounced effect observed under combined therapy, approaching values of intact animals. Conclusion: Interstitial lung injury is accompanied by interconnected local and systemic metabolic disturbances that contribute to disease progression. Combined pharmacological correction demonstrates a pronounced normalizing effect, highlighting its potential as an effective therapeutic strategy.